Changing teaching, changing teachers : 21st century teaching and learning through lesson and learning study - Wood, Keith (Professor); Sithamparam, Saratha (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"A unique feature of this book is its focus on engaging teachers themselves in changing teaching as a way to bring about teacher change through Lesson and Learning Study. The sequence - changing teaching, changing teachers - is significant. This approach to professional development is not about telling teachers what and how they should teach to bring about change in their students' learning outcomes. It is about empowering teachers to make their own decisions about what needs to change. Empowering teachers in this way has been identified as the 'soul' of Japanese Lesson Study (Cheng, forthcoming). It is the soul which can so easily be compromised when Lesson Study is adopted and - inevitably it seems - adapted in new contexts around the globe. Without teacher empowerment, top-down curriculum development is almost bound to fail. In presenting the cases of collaborative professional development included in this book, care has been taken to include the teachers' voices. They are intended to be the subjects and not the objects of our research into teachers' professional development"--
Changing Teaching, Changing Teachers -- The Many Faces of Lesson Study -- Learning Study -- st Century Teaching and Learning Design -- Learning and Variation -- Critical Aspects of the Object of Learning -- Roles of Teacher, Researcher, Facilitator, Coach -- Necessary Conditions of Teacher Learning.
OCLC-licensed vendor bibliographic record.
Keywords: Teachers -- Training of; Teachers -- In-service training; Educational change; Teachers -- Professional relations; Curriculum planning; EDUCATION / Teaching Methods & Materials / General; EDUCATION / General